1994
DOI: 10.1111/j.1432-1033.1994.tb18847.x
|View full text |Cite
|
Sign up to set email alerts
|

The process of cellular uptake of iron from transferrin

Abstract: In an attempt to improve our understanding of the complex interplay between cell compartments and chemical species during cellular uptake of iron from transfenin, we designed a computer simulation program based on current models of receptor-mediated endocytosis and pinocytosis. The program calculates and visualizes, as a function of time, the changes in transfenin, apotransferrin, and iron concentrations occurring in all relevant cellular compartments during cellular iron acquisition from transferrin. Simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Several studies have indicated the presence of a nonspecific, non-receptor-mediated iron-uptake mechanism [2-41. Recently, it was suggested that the main difference in iron-uptake mechanism between hepatocytes and reticulocytes was the former's ability to utilize pinocytosis for iron uptake from transferrin [8]. Many components taken up by cells via pinocytosis enter the lysosomal compartment and are subsequently degraded [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated the presence of a nonspecific, non-receptor-mediated iron-uptake mechanism [2-41. Recently, it was suggested that the main difference in iron-uptake mechanism between hepatocytes and reticulocytes was the former's ability to utilize pinocytosis for iron uptake from transferrin [8]. Many components taken up by cells via pinocytosis enter the lysosomal compartment and are subsequently degraded [21].…”
Section: Discussionmentioning
confidence: 99%
“…By utilizing a computer program [8] the uptake of '%labelled N-fragment could be simulated with rate constants similar to those published for pinocytosis in hepatocytes. This argues in favour of pinocytosis as the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Also, transferrin may be internalized by a low affinity system, possibly pinocytotic (Hodgson et al, 1994), that is receptor independent and capable of delivering iron to haemoglobin. The latter pathway appears to be a minor pathway in reticulocytes (Bakoy & Thorstensen, 1994).…”
Section: Discussionmentioning
confidence: 91%